The Salem witch trials : mass hysteria and many lives lost - Burgan, Michael (Tangled history., 2019)
Discusses the Salem Witch Trials of 1692, focusing on Salem's Puritan belief system, accusations, trials, executions, and people involved. Includes illustrations, critical thinking questions, a timeline, a glossary, and further resources.